CeMo2B5: A New Type of Arrangement of Puckered Boron Hexagonal Rings. Issue 31 (12th August 2019) - Flipo, Sever; Kohout, Miroslav; Roth, Friedrich; Weigel, Tina; Schnelle, Walter; Bobnar, Matej; Ormeci, Alim; Burkhardt, Ulrich; Hennig, Christoph; Leisegang, Tilmann; Meyer, Dirk‐Carl; Leithe‐Jasper, Andreas; et al.
Abstract : RE Mo2 B5 ( RE = Ce, Pr, Nd) and CeW2 B5 have been synthesized by arc melting with further annealing at 1300 °C. CeMo2 B5 crystallizes in a new structure type with space group Pnma, a = 11.0298(2) Å, b = 3.12080(5) Å, c = 9.9594(2) Å, Z = 4. Its structural arrangement reveals puckered [B6 ]‐hexagonal rings, trigonal‐prismatic‐ and empty pyramidal‐tetrahedral‐slabs. The structure can be related to the derivatives of AlB2 and CrB prototypes. The boron atoms form a two‐dimensional network of corrugated ribbons, each composed of four edge‐linked [B6 ] rings infinitely extending along the b ‐axis. CeMo2 B5 is a Pauli paramagnet. Electrical transport measurements together with the calculated density of states at the Fermi level of 3.81 states eV –1 f.u. –1 indicate CeMo2 B5 to be a typical metallic system. Electronic structure calculations reveal significant hybridization of Ce 4 f 5 d states with Mo 4 d states. The chemical bonding scenario is dominated by chains of [Ce2 Mo2 ] clusters with multi‐center bonds. These clusters are connected via metallic Mo–Mo bonds. This metal‐framework, in turn, is stabilized by bonding interactions with the boron ribbons to which it donates electrons. Abstract : CeMo2 B5 is a simple metallic system whose bonding architecture is dominated by chains of [Ce2 Mo2 ] clusters with multi‐center bonds. The structural, magnetic, electronic transport properties are reported, and the chemical bonding situation is analyzed by theoretical DFT calculations.